Public Health. - Anza-Ramirez,C; Cardenas,MK; Landeiro,F; Montesinos,R; Custodio,N; Da,Re M; Calvo,RA; Belon-Hercilla,V; Cuba,MS; Bernabe,A; Butler,C; Miranda,J; et al. (Alzheimers Dement, 2024)
BACKGROUND: Dementia is a global health challenge, especially in low- and middle-income countries like Peru, where diagnosis, access, and awareness are limited. Within the IMPACT Dementia project, a component focuses on developing, testing, and implementing an mHealth-enabled system for dementia screening and diagnosis, and assessing its cost-effectiveness. METHODS: Phase I. To develop a dementia diagnostic screening mHealth system: The features of the screening tool will be locally adapted using a co-design approach including community members and community health workers (CHW) in four regions in Peru (Lima, Tumbes, Iquitos, and Huancayo) to enhance adaptability and efficacy. The final tool will be applied to older adults (60+) in the community by CHW. PHASE II: To assess the accuracy and acceptability, and characterization of older adults (60+) at the population level in Peru (n≈32,000): Using the mHealth system developed in Phase I, assessments including AD8, RUDAS-PE, and PFAQ, will be conducted. Accuracy for dementia diagnosis will be determined through gold-standard assessments involving interviews, neuropsychological testing, and the CDR in a subgroup of participants conducted by neurologists. The system will also collect data on socio-demographic information, carers, co-morbidities, quality of life, resource usage and costs. Phase III. To integrate the mHealth diagnostic system into Peru's primary healthcare (PHC) level: After validation, a 3-month quasi-experimental study in 2 centres per region will assess system performance, using waiting room recruitment and provider-conducted screenings for older adults. Indicators will evaluate integration success, sensitivity, and specificity of the tool, cost-effectiveness, and stakeholder perspectives through a process evaluation, guiding future scalability. RESULT: Early phases suggest that the IMPACT Dementia project will offer insights into dementia challenges in Peru. The co-design phase prioritises cultur